The Earliest Known Radiation of Pitheciine Primates - Novo, Nelson Martin (2025)
Two of the more interesting and controversial platyrrhine primate taxa from the Miocene of Patagonia are Soriacebus andMazzonicebus. Although they are known basically from isolated teeth and partial mandibles and maxillae, their morphology ishighly distinctive. Opinions about their phylogenetic relationships differ widely. We interpret these fossils as belonging to thelineage of the anatomically derived, living pitheciine seed‐predators; others hold the view that they are stem platyrrhines withconvergent adaptations with pitheciines (with the single exception of Proteropithecia among the Patagonian forms), somewhatdistant relatives converging coincidently with pitheciines. Here we tested these hypotheses in two ways: (1) by summarizing acharacter analysis of taxonomically informative traits; (2) we implemented “blind” parsimony analyses using the softwarepackage TNT, including a combined matrix of both morphological and molecular data, and replication studies of other matrices.We make some criticisms on the applied methodology of Parsimony in our analysis. Soriacebus and Mazzonicebus resultedsister‐taxa nested deeply within the pitheciid clade; thus, and according to our inferences, they are not stem platyrrhines. Mostof the differences separating them from the younger and uniformly recognized pitheciine fossils Proteropithecia, Nuciruptor andCebupithecia are explained as being of more primitive character states; the vast majority of resemblances and their broaderfunctional patterns are definitively pitheciine, as typified by the living pitheciines (sakis and uakaris). We therefore found thatnone of the Miocene Patagonian genera treated here can be reliably interpreted as stem platyrrhines. Rather, they tend to ratifythe Long Lineage Hypothesis.